Production of Cellulose Nanofiber (Cnf) from Empty Fruit Bunch (EFB) via mechanical method - Muhammad Arif Fahmi, Supian; Khairatun Najwa, Mohd Amin; Saidatul Shima, Jamari; Shahril, Mohamad (Elsevier Ltd, 2019)
The palm oil production in Malaysia contributes 85.5% of the total biomass production in Malaysia. From the 85.5%, empty fruit bunch (EFB) are the most that contribute to biomass waste produced [1]. With the increasing number of empty fruit bunch (EFB) produced annually, it has raises massive environment concern. Empty fruit bunch (EFB) biomass is made up of cellulose (24-65%), hemicellulose (21-34%), and lignin (14-31%) [2]. Thus it has a great potential to use the cellulose source for the production of cellulose nanofiber (CNF) and changing biomass by-product to a value added product . Besides that, currently the main raw materials for cellulose production are from wood and cotton linter. However it will promote deforestation and accelerate the greenhouse effect. Therefore, empty fruit bunch (EFB) is a great candidate for the future cellulose raw material. In addition, recent technology in cellulose production requires a high amount of production cost due to its chemical treatment and it is not environmentally friendly. Hence the implementation of the mechanical method will decrease the amount of energy and chemical as well as it is more environmentally friendly. In addition, the cellulose was also initially extracted via steam explosion pretreatment. The steam explosion pretreatment technology also has low energy consumption [3]. Mechanical treatment has been proven to be the best treatment for producing cellulose nanofiber (CNF) [4].